Pengaruh Profitabilitas, Leverage, Likuiditas, dan Pertumbuhan Penjualan Terhadap Agresivitas Pajak Pada Perusahaan Manufaktur di Indonesia - Pertiwi, Vira; Sihono, Agus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
From 2019 to 2023, this study examines how tax aggressiveness affects profitability, leverage, liquidity, and sales growth in Indonesia Stock Exchange (IDX) pharmaceutical manufacturing companies. This study sampled nine pharmaceutical companies using purposive sampling. SPSS performed multiple linear regression. Researcher found no correlation between liquidity and tax aggressiveness. Conversely, profitability and leverage negatively affect tax aggressiveness, while sales growth has a positive impact. These findings suggest that certain financial conditions do not directly drive companies to engage in aggressive tax practices. Profitable businesses tend to be more compliant with tax obligations. The results highlight the importance of evaluating tax management strategies based on transparency and compliance principles. Furthermore, shareholders should assess potential tax aggressiveness comprehensively, rather than relying solely on financial metrics.